TEKNIK REINFORCEMENT UNTUK MENINGKATKAN MOTIVASI PADA ANAK TUNAGRAHITA YANG MENGALAMI KESULITAN (DYSCALCULIA LEARNING) DI SEKOLAH LUAR BIASA NEGERI BANJARNEGARA - Hanim Masruroh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
A habit that is rarely carried out by educators when the teaching and learning process is in progress, namely providing reinforcement to students or students, it is rare to find teachers saying excellent words and giving thumbs up for students who successfully answer questions posed by the teacher.Based on this, the researchers formulated the following problem formulations (1) How is the implementation of reinforcement techniques to increase motivation for mentally retarded children who have difficulty calculating (dyscalculia learning) at the Banjarnegara Special School? (2) What are the results of implementing reinforcement techniques to increase motivation in mentally retarded children who have difficulty calculating (dyscalculia learning) at the Banjarnegara Special School?This research uses a qualitative research method with a case study approach. Data collection techniques using interviews, observation, and documentation. The data that the researchers got in the field were then diagnosed, followed by prognosis, then implementation of therapy, and finally evaluation. The data from the counseling results were then analyzed using comparative descriptive, namely the analysis of the results of the study by comparing the counselee's behavior before and after the counseling process was carried out through the reinforcement technique.The research resulted in several conclusions, namely: 1). There are five steps of the counseling process that have been carried out, namely: the first step is identification of the problem, the second step is diagnosis, the third step is prognosis, the fourth step is therapy or treatment, and the last is follow-up. 2). Changes made by counselors and counselees were quite successful with a percentage of 75%. This is in accordance with the standard of the test which is classified as quite successful, this can be seen from the change from the counselee who is quite capable in the flow of calculations, the operation of mathematical questions although it still needs guidance and direction to be more active. Kebiasaan yang jarang dilakukan oleh pendidik ketika proses belajar mengajar sedang berlangsung yaitu memberikan penguatan (reinforcement) kepada anak didik atau siswa, jarang menjumpai guru mengucapkan kata bagus sekali dan mengacungkan jempol untuk siswa yang berhasil menjawab pertanyaan yang dilontarkan guru.Berdasarkan hal tersebut, maka peneliti merumuskan rumusan masalah sebagai berikut (1) Bagaimana pelaksanaan teknik reinforcement untuk meningkatkan motivasi pada anak tunagrahita yang mengalami kesulitan menghitung (dyscalculia learning) di Sekolah Luar Biasa Negeri Banjarnegara? (2) Bagaimana hasil pelaksanaan teknik reinforcement untuk meningkatkan motivasi pada anak tunagrahita yang mengalami kesulitan menghitung (dyscalculia learning) di Sekolah Luar Biasa Negeri Banjarnegara?Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Data yang peneliti dapatkan di lapangan kemudian didiagnosis, dilanjutkan dengan prognosis, kemudian pelaksanaan terapi, terakhir evaluasi. Data hasil dari konseling selanjutnya dianalisis dengan deskriptif komparatif, yaitu analisis hasil penelitian dengan membandingkan perilaku konseli sebelum dan sesudah dilakukan proses konseling melalui teknik reinforcement.Penelitian menghasilkan beberapa kesimpulan yaitu: 1). Terdapat lima langkah proses konseling yang telah dilakukan yaitu: langkah pertama identifikasi masalah, langkah kedua diagnosis, langkah ketiga prognosis, langkah keempat terapi atau treatment, dan yang terakhir follow up. 2). Perubahan yang dilakukan oleh konselor dan konseli yang dapat dikatakan cukup berhasil dengan presentase 75 %. Hal ini sesuai dengan standart uji yang tergolong dalam kategori cukup berhasil, hal ini dapat dilihat adanya perubahan dari konseli yang cukup mampu dalam alur hitungannya, pengoperasian soal matematik meskipun masih perlu bimbingan dan arahan agar menjadi lebih giat.